1999
DOI: 10.1046/j.1365-2044.1999.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating in labour. A randomised controlled trial assessing the risks and benefits

Abstract: SummaryThe aim of this study was to determine whether permitting women in labour to eat a light diet would: (i) alter their metabolic profile, (ii) influence the outcome of labour, and (iii) increase residual gastric volume and consequent risk of pulmonary aspiration. Women were randomised to receive either a light diet (eating group, n ¼ 48) or water only (starved group, n ¼ 46) during labour. The light diet prevented the rise in plasma b-hydroxybutyrate (p ¼ 2.3 × 10 ¹5 ) and nonesterified fatty acids (p ¼ 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 31 publications
1
75
0
3
Order By: Relevance
“…Hence, fasting such patients will never make them 'fasted and elective'. The same applies to pregnant women in labour (50).…”
Section: Patient Groups Exempt From the Liberal Fasting Guidelinesmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, fasting such patients will never make them 'fasted and elective'. The same applies to pregnant women in labour (50).…”
Section: Patient Groups Exempt From the Liberal Fasting Guidelinesmentioning
confidence: 95%
“…Despite this fact, most maternity wards encourage oral intake during labour (50). This may sound counter-productive for us as anesthesiologists, but to obstetricians, midwives and the women themselves, the small risk of an emergency Caesarean-section under general anaesthesia may not be a valid argument to impose unphysiological starvation during a natural process with a large need for calories (50).…”
Section: Patient Groups Exempt From the Liberal Fasting Guidelinesmentioning
confidence: 99%
“…Of these, we have included five studies involving 3130 women in this review (Kubli 2002;Scheepers 2002;Scrutton 1999;Tranmer 2005), excluded two studies (Scheepers 2004;Shennan 2005 ) and assigned four studies as awaiting classification; we have attempted to contact these authors (Goodall 1999;Laifer 2000;Yiannouzis 1994;Zhao 1996).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The authors included 5 randomized trials that compared different interventions restricting oral intake vs free oral intake: 2 studies compared a restrictive policy including the possibility of drinking water to a policy encouraging women to eat and drink during labor [71,72]; 2 studies compared women who had only water with those who drank fluid carbohydrates during labor [73,74]; and another compared a restrictive policy with no fluid intake to a policy allowing women to eat and drink as they chose during labor [75]. The authors found no difference in oxytocin use between women subject to the restrictive policies and those for whom oral intake was authorized (n=3103; RR 1.02, 95% CI 0.95-1.09).…”
Section: Oral Hydration and Solid Food During Labormentioning
confidence: 99%